Mesoscale Eddies Structure Mesopelagic Communities - Della Penna, Alice; Gaube, Peter (Frontiers in Marine Science, 2020)
Mesoscale eddies play a key role in structuring open ocean ecosystems, affecting the entire trophic web from primary producers to large pelagic predators including sharks and elephant seals. Recent advances in the tracking of pelagic predators has revealed that these animals forage in the mesopelagic and the depth and duration of their foraging dives are affected by the presence of eddies. The ways in which eddies impact the distribution of mesopelagic micronekton, however, remain largely unknown. During a multi seasonal experiment we used a shipboard scientific echosounder transmitting at 38 kHz to observe the distribution of acoustic backscattering in the energetic mesoscale eddy field of the northwestern Atlantic. Observations were collected at 24 stations with 6 located in anticyclonic and 7 in cyclonic eddies. The sampled anticyclonic eddies are characterized by intense acoustic backscattering in the mesopelagic and changes in the intensity of acoustic backscattering layers match gradients of surface properties. Furthermore, mesopelagic daytime backscattering is positively correlated with sea level anomaly. These results suggest that anticyclonic eddies in the northwestern Atlantic impact the distribution of mesopelagic micronekton and may have the potential to locally enhance or structure spatially mesopelagic communities.